2019
DOI: 10.11648/j.ajac.20190704.13
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Anti-nutritional Composition of <i>Ximenia americana</i> Fruit

Abstract: In this work the nutritional and anti-nutritional composition of Ximenia americana fruit is investigate using standard analytical methods. The results of proximate analysis of the fruit on dry weight basis shows that it contains, Crude protein (7.26%), Crude lipid (13.0%), ash (10.5%), and moisture (64%Wet Weight), The pulp contains appreciable concentration of ascorbic acid (21.12 mg/100g). The mineral analysis, revealed that the pulp is rich in potassium (690mg/100g), magnesium (10.67mg/100g) phosphorus (4.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
(22 reference statements)
1
8
4
Order By: Relevance
“…(2015) . However, the study fruit had lower values of ash content with the reported value of Muhammad et al. (2019) .…”
Section: Resultscontrasting
confidence: 64%
See 4 more Smart Citations
“…(2015) . However, the study fruit had lower values of ash content with the reported value of Muhammad et al. (2019) .…”
Section: Resultscontrasting
confidence: 64%
“…Significant regional differences were also observed on protein content of X. americana fruit from South America to Africa. The study fruit fleshs showed higher protein content as compared to the reported value by Lockett (2000) ; Muhammad et al. (2019) and Sarmento et al.…”
Section: Resultsmentioning
confidence: 45%
See 3 more Smart Citations